Strategies used by PRDCI in managing conflict between upstream and downstream farmers in the Magapa-Suague River basin - Cataya, Carrell L.
This stduy describes the different strategies used by PRDCI in managing conflict between upstream farmers in the Magapa-Suage River Basin. It seeks to identify the causes of conflict and the conlict management strategies used and their effects on the stakeholders. The role of PRDCI in the management of the river basin was also described. The study was conducted in the municipalities of Mina, Pototan, Maasin, Badiangan, New Lucena and Janiuay. Ten key respondents were interviewed using two sets of open-ended interview schedule. The results were analyzed using descriptive statistics. The results showed that the conflict was caused by the shortage of water supply due to the depleted condition of the river. In addition, the conflict was heightened by the upstream farmers' practice of diverting water from the river going to their farms., In managing the conflict, PRDCI initiated the effort to rehabilitate the river and its uses participatory strategies such as meetings, conferences and consultations. Community organizing, conscientization, net working and mass mobilization were also used. Eventually, the Magapa-Suague River Management Council was created that is now spearheading the initiative to rehabilitate the river. At present, the conflict is downsized by the river rehabilitation effort. The study concludes that conflict management is a complicated process that requires skills and abilities such as sensitivity and patience. Furthermore, in conflict management, a joint effort among the people, the government agencies as well as the non-government organization is also indispensable